Generalizing About Striking Properties: Do Glippets Love to Play With Fire? - Lazaridou-Chatzigoga, Dimitra; Katsos, Napoleon; Stockall, Linnaea (Frontiers in Psychology, 2019)
Two experiments investigated whether 4- and 5-year-old children are sensitive to whether the content of a generalisation is about a salient or noteworthy property (henceforth ‘striking’) and to whether varying the number of exceptions has any effect on children’s willingness to extend a property after having heard a generalization. Moreover, they investigated how the content of a generalisation interacts with exception tolerance. Adult data were collected for comparison. We used generalisations to describe novel kinds (e.g. ‘glippets’) that had either a neutral (e.g. ‘play with toys’) or a striking property (e.g. ‘play with fire’) and measured how willing participants were to extend the property to a new instance of the novel kind. Experiment 1 demonstrated that both adults and children show sensitivity to strikingness in that striking properties were extended less than neutral ones, although children extended less than adults overall. The responses of both age groups were significantly different from chance. Experiment 2 introduced varying numbers of exceptions to the generalisation made (minimal: 1 exception; maximal: 3 exceptions). Both adults and children extended both types of properties even in the face of exceptions, but to a lower degree than in experiment 1. Striking properties were extended less than neutral ones, as in experiment 1. We observed that the greater the number of exceptions, the lower the rates of extension we obtained, for both types of properties in adults, but only with striking properties in children. Children seemed to keep track of varying numbers of exceptions for striking properties, but their performance did not differ from chance. The findings underscore that 4- and 5-year olds are sensitive to strikingness and to exception tolerance for generalisations and are developing towards an adult-like behaviour with respect to the interplay between strikingness and exception tolerance when they learn about novel kinds. We discuss the implications of these results with regards to how children make generalisations.